Sox10 is an active nucleocytoplasmic shuttle protein, and shuttling is crucial for Sox10-mediated transactivation - Wegner, Michael; Stamminger, Thomas; Glaser, Gabriele; et al. (Molecular and Cellular Biology, 2002)
Sox10 belongs to a family of transcription regulators characterized by a DNA-binding domain known as the HMG box. It plays fundamental roles in neural crest development, peripheral gliogenesis, and terminal differentiation of oligodendrocytes. In accord with its function as transcription factor, Sox10 contains two nuclear localization signals and is most frequently detected in the nucleus. In this study, we report that Sox10 is an active nucleocytoplasmic shuttle protein, competent of both entering and exiting the nucleus. We identified a functional Rev-type nuclear export signal within the DNA-binding domain of Sox10. Mutational inactivation of this nuclear export signal or treatment of cells with the CRM1-specific export inhibitor leptomycin B inhibited nuclear export and consequently nucleocytoplasmic shuttling of Sox10. Importantly, the inhibition of the nuclear export of Sox10 led to decreased transactivation of transfected reporters and endogenous target genes, arguing that continuous nucleocytoplasmic shuttling is essential for the function of Sox10. To our knowledge this is the first time that nuclear export has been reported and shown to be functionally relevant for any Sox protein.
UnivIS-Import:2015-03-09:Pub.2002.med.IB.LPCIPDBI.sox10i